2016
DOI: 10.1016/j.dadm.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Activities of Daily Living Questionnaire and the Montreal Cognitive Assessment

Abstract: IntroductionThe Activities of Daily Living Questionnaire (ADL-Q) is an informant report questionnaire assessing functional impairment in daily living skills. Previous research has demonstrated correlations between ADL-Q and cognitive screening measures among patients with dementia. This study examined the relationship between ADL-Q and the Montreal Cognitive Assessment (MoCA), a brief cognitive screening.MethodsRecords of 448 individuals from an outpatient neurology clinic were reviewed. Pearson correlations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
4
16
0
1
Order By: Relevance
“…Many studies have utilized MoCA for assessing cognitive function related to the patient's functional impairment [ 17 18 ]. Schweizer et al [ 30 ] reported that MoCA was more sensitive than MMSE in detecting cognitive impairment after hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have utilized MoCA for assessing cognitive function related to the patient's functional impairment [ 17 18 ]. Schweizer et al [ 30 ] reported that MoCA was more sensitive than MMSE in detecting cognitive impairment after hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…However, existing studies on MoCA and functional outcome were mostly performed on elderly patients with heterogeneous diseases and mild functional impairment. Durant et al [ 17 ] found that lower a MoCA score was associated with greater functional impairment in neurodegenerative diseases, including Alzheimer disease, mild cognitive impairment, cognitive disorder, Lewy body dementia, vascular dementia, etc. However, these studies had the limitation of being a heterogeneous clinical sample, focusing on current function rather than the recovery of the patient's function.…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 28 MoCA scores have also been shown to correlate with the Activities of Daily Living Questionnaire 29 a measure of functional integrity in dementia. 30 The MoCA has the further advantage of yielding not only a total score (overall measure) but also index scores based on individual items tapping domains of attention, retentive memory, orientation, language, and executive function. 31 …”
Section: Methodsmentioning
confidence: 99%
“…Their physical status, major vascular risk factors [22], and neurological syndromes were assessed. The severity of cognitive impairment was determined concurrently using the Montreal Cognitive Assessment (MoCA) scale and independence in everyday life [23]. Dementia was diagnosed if the MoCA score was <26 points and the patient was dependent on others; cognitive impairment was considered mild if the score was <26 points and the patient was independent.…”
Section: Methodsmentioning
confidence: 99%